Good Practices of Making Art and Culture Accessible to the Deaf and Hard of Hearing at the Deafland Exhibition in the Silesian Museum in Katowice - Kołodziejczak, Agnieszka (Protection of Cultural Heritage, 2022)
Accessibility of culture and art to the deaf and hard of hearing is the topic of the doctoral dissertation prepared by the author under the supervision of Professor Aneta Pawlowska in the Doctoral School of Humanities at the University of Lodz' and the “Ja-Ty-My” Social Support Association, entitled “The Problem of Accessibility of Information in Public Institutions and Social Economy Entities in the Field of Culture and Art for People with Hearing Loss and Disabilities in Poland. Recommendations and standards.” This chapter adopts the insider perspective of a deaf researcher to examine the issue of broadly understood accessibility basing on the Deaﬂand [Glusza] exhibition at the Silesian Museum in Katowice. It is a breakthrough show in Poland in terms of the subject matter and the use of available technical solutions for people with special needs.